2016
DOI: 10.1152/ajpgi.00441.2015
|View full text |Cite|
|
Sign up to set email alerts
|

The serine protease-mediated increase in intestinal epithelial barrier function is dependent on occludin and requires an intact tight junction

Abstract: Barrier dysfunction is a characteristic of the inflammatory bowel diseases (IBD), Crohn's disease and ulcerative colitis. Understanding how the tight junction is modified to maintain barrier function may provide avenues for treatment of IBD. We have previously shown that the apical addition of serine proteases to intestinal epithelial cell lines causes a rapid and sustained increase in transepithelial electrical resistance (TER), but the mechanisms are unknown. We hypothesized that serine proteases increase ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 78 publications
0
28
1
Order By: Relevance
“…While serine proteases have been suggested to mediate such effect through PKCζ activation, this level of regulation remains poorly understood. A key role in maintaining epithelial homeostasis was also ascribed to matriptase and prostasin, two serine proteases with trypsin‐like activity 41‐45 . In these studies, matriptase depletion, either by RNAi silencing in epithelial cells or genetic downregulation in St14 hypomorphic mice, compromises TJ and increases intestinal paracellular permeability 41,42 .…”
Section: Serine Proteases In a Nutshellmentioning
confidence: 99%
“…While serine proteases have been suggested to mediate such effect through PKCζ activation, this level of regulation remains poorly understood. A key role in maintaining epithelial homeostasis was also ascribed to matriptase and prostasin, two serine proteases with trypsin‐like activity 41‐45 . In these studies, matriptase depletion, either by RNAi silencing in epithelial cells or genetic downregulation in St14 hypomorphic mice, compromises TJ and increases intestinal paracellular permeability 41,42 .…”
Section: Serine Proteases In a Nutshellmentioning
confidence: 99%
“…23 Based on studies in different epithelial cells, occludin seems to play a role in epithelial wound healing, 24 apoptosis 25 and to be important to the interaction with intraepithelial lymphocytes. 26 Studies addressing occludin's role in barrier function have suggested involvement in serine proteasedependent barrier modulation, 27 hypoxia-induced, 28 ethanol-induced 29 and hydrogen peroxideinduced reduction in barrier function. 30,31 Occludin and the epithelial leak pathway Interestingly, several studies observed no effect of occludin expression on basal flux of solutes across epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported that Ca 2+ reintroduction recovered TER values and increased TJ integrity in EGTA-treated cells (Farshori and Kachar, 1999 ; Ronaghan et al, 2016 ). Therefore, we performed a calcium switch assay to examine the effect of TJ integrity on C. jejuni invasion.…”
Section: Resultsmentioning
confidence: 87%